Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12870-021-03086-3
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of the wheat transcriptome in response to infection with Claviceps purpurea, the causal agent of ergot

Abstract: Background Ergot, caused by the fungal pathogen Claviceps purpurea, infects the female flowers of a range of cereal crops, including wheat. To understand the interaction between C. purpurea and hexaploid wheat we undertook an extensive examination of the reprogramming of the wheat transcriptome in response to C. purpurea infection through floral tissues (i.e. the stigma, transmitting and base ovule tissues of the ovary) and over time. Results C. pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 85 publications
0
5
0
12
Order By: Relevance
“…It was previously taken for granted that ergot infection does not cause any defense reactions in rye. However, recent transcriptomic studies showed that in both wheat and rye, the host plant responds to the infection by upregulating defense-related genes, precisely when the germ tube reaches the ovary [73,74]. Thus, the host obviously recognizes the Claviceps infection.…”
Section: How To Proceed In Future Breedingmentioning
confidence: 99%
“…It was previously taken for granted that ergot infection does not cause any defense reactions in rye. However, recent transcriptomic studies showed that in both wheat and rye, the host plant responds to the infection by upregulating defense-related genes, precisely when the germ tube reaches the ovary [73,74]. Thus, the host obviously recognizes the Claviceps infection.…”
Section: How To Proceed In Future Breedingmentioning
confidence: 99%
“…Как уже отмечалось, эргоалкалоиды сыграли существенную роль в распространении спорыньи и расширении ареала этого аскомицета. C. purpurea пора-жает ряд экономически значимых зерновых культур, в том числе рожь, пшеницу и ячмень (19,49,147). Спорынья инфицирует злаки во время цветения, заражая ткани неоплодотворенных соцветий женских растений и заменяя семена склероциями (53,147).…”
Section: рис 2 искусственно воспроизведенный оптимальный путь биосинт...unclassified
“…Спорынья инфицирует злаки во время цветения, заражая ткани неоплодотворенных соцветий женских растений и заменяя семена склероциями (53,147). Таким образом, перекрестноопыляющиеся злаки, которые демонстрируют открытое цветение, такие как рожь, особенно подвержены риску заражения (49,148). Спорынья инфекционна и для гибридных форм ячменя или пшеницы, получивших чувствительность как побочный результат селекции (49,149,150).…”
Section: рис 2 искусственно воспроизведенный оптимальный путь биосинт...unclassified
See 2 more Smart Citations